Nitrogen oxide purification method
The use of a metal-supported zeolite catalyst with an 8-membered ring structure addresses the low-temperature nitrogen oxide purification challenges faced by existing catalysts, achieving enhanced NO conversion rates and stability.
Patent Information
- Application Number
- JP2020217611
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-25
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2040-12-25
AI Technical Summary
Existing catalysts, such as perovskite and Cu/ZSM-5, face challenges in efficiently purifying nitrogen oxides at low temperatures, particularly in automobile exhaust gases, due to low catalytic activity and rapid activity deterioration.
A method using a catalyst with a metal supported on a zeolite having an 8-membered ring structure, with a molar ratio of metal to Al in the zeolite ranging from 0.5 to 2.0, to enhance nitrogen oxide purification efficiency at low temperatures.
The catalyst achieves a higher conversion rate of NO in exhaust gases compared to conventional Cu/ZSM-5 catalysts, while minimizing the intrusion of large hydrocarbons and maintaining catalytic activity over time.
Smart Images

Figure 0007669692000005 
Figure 0007669692000001 
Figure 0007669692000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for purifying nitrogen oxides using a nitrogen oxide purification catalyst, and is applicable, for example, to the purification of nitrogen oxides contained in exhaust gases emitted from internal combustion engines of automobiles, factories, power plants, etc. [Background technology]
[0002] Automobile engines, as well as internal combustion engines in factories and power plants, are often operated under conditions of excess oxygen to improve fuel efficiency. Under conditions of excess oxygen, nitrogen oxides (NO X "). Nitrogen oxides are not only harmful in themselves, but are also known to be a cause of photochemical oxidants. Therefore, it is necessary to purify the nitrogen oxides contained in exhaust gas, especially nitric oxide (NO).
[0003] Known conventional technologies for purifying NO include a removal method that uses a combination of a catalyst and a reducing agent such as ammonia, hydrocarbon, or hydrogen, and a method that directly decomposes NO into nitrogen (N2) and oxygen (O2) using only a catalyst without using a reducing agent. In particular, the latter direct decomposition method using only a catalyst is considered to be the most preferable for decomposing NO in exhaust gases emitted from automobile engines, from the standpoint of the simplicity of the equipment, etc.
[0004] As catalysts for purifying nitrogen oxides for use in the direct decomposition method, zeolite-based, perovskite-based, and other catalysts have been reported so far (Non-Patent Documents 1 to 3). Also, a zeolite catalyst in which Cu is supported on AEI zeolite has been disclosed (Patent Document 1). [Prior art documents] [Non-patent literature]
[0005] [Non-Patent Document 1] Journal of the Chemical Society of Japan 1991 Vol.5, 574-583 [Non-Patent Document 2] Comptes Rendus Chimie, 19, 1254-1265(2016) [Non-Patent Document 3] Catalysis Today, 281, 566-574(2017) [Patent documents]
[0006] [Patent Document 1] JP 2017-81809 A Summary of the Invention [Problem to be solved by the invention]
[0007] Perovskite catalysts used as catalysts in the direct decomposition method have excellent heat resistance, so it is thought that they can be used to purify nitrogen oxides contained in exhaust gases emitted at high temperatures of over 800°C, such as factory exhaust gases. However, they have an issue of low catalytic activity in the temperature range of 300 to 400°C, such as automobile exhaust gases, and the range of application is limited. On the other hand, Cu / ZSM-5 is known as a zeolite catalyst, and it shows high catalytic activity even in the temperature range of 300 to 400°C (Non-Patent Documents 1 and 2). However, although the application of Cu / ZSM-5 to the direct decomposition reaction of NO was first reported in the 1980s, it did not achieve the catalytic activity required for practical use, and it was difficult to improve the activity. Furthermore, there is also the issue that the performance of the catalytic activity deteriorates rapidly over time, so there is still no prospect of practical use.
[0008] Recently, a method has been reported in which Fe / zeolite is used as a catalyst and microwaves (MW) are used to instantaneously heat the catalyst to purify nitrogen oxides (Non-Patent Document 3). However, it is thought that this method will be difficult to put into practical use, since it requires the installation of a MW in, for example, an automobile, and therefore also requires an energy supply source.
[0009] The present inventors also succeeded in synthesizing an AEI zeolite with a low Si / Al ratio and high crystallinity, and disclosed a zeolite catalyst in which Cu was supported on the AEI zeolite (Patent Document 1). It has been found that the catalyst has extremely excellent denitration performance when used with a reducing agent.
[0010] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a method for purifying nitrogen oxides, particularly NO, contained in exhaust gas, with high efficiency even at low temperatures. [Means for solving the problem]
[0011] The present inventors have discovered that in an atmosphere containing nitrogen oxides, nitrogen oxides can be efficiently purified by using a catalyst in which a metal that serves as an active site is supported on a zeolite having an eight-membered ring structure in a molar ratio of 0.5 to 2.0 relative to Al in the zeolite, and have arrived at the present invention. That is, the present invention provides the following [1] to [9]. [1] A method for purifying nitrogen oxides, which comprises contacting nitrogen oxides contained in a gas with a zeolite carrying a metal to remove the nitrogen oxides, characterized in that the zeolite has an eight-membered ring structure and the molar ratio of the amount of metal carried to Al in the zeolite is 0.5 to 2.0. [2] The method for purifying nitrogen oxides according to the above [1], wherein the zeolite is an aluminosilicate zeolite. [3] The method for purifying nitrogen oxides according to the above [2], wherein the zeolite has a SiO2 / Al2O3 (molar ratio) of 3 to 100. [4] The method for purifying nitrogen oxides according to the above [2] or [3], wherein the zeolite is any one of AEI type, CHA type, AFX type, and RHO type. [5] The method for purifying nitrogen oxides according to any one of the above [1] to [4], wherein the metal supported on the zeolite is at least one selected from the group consisting of Cu and Fe. [6] The method for purifying nitrogen oxides according to any one of the above [1] to [5], wherein the amount of the metal supported on the zeolite is 1 to 15 parts by mass per 100 parts by mass of the catalyst. [7] The method for purifying nitrogen oxides according to any one of the above [1] to [6], wherein a reducing agent is used in a molar ratio of 0.1 or less to the nitrogen oxides contained in the gas. [8] The method for purifying nitrogen oxides according to the above [7], wherein the ratio of the total molar amount of the nitrogen-containing reducing agent to the total molar amount of the reducing agents is 0.1 or less. [9] The method for purifying nitrogen oxides according to any one of the above [1] to [8], wherein the amount of nitrogen oxides in the gas is 10 to 10,000 ppm by volume. Effect of the Invention
[0012] According to the present invention, a catalyst in which a zeolite having an 8-membered ring structure (hereinafter sometimes referred to as "8-membered ring zeolite") is supported so that the content of metal (hereinafter sometimes referred to as "M") relative to Al in the zeolite (M / Al, molar ratio) is 0.5 to 2.0 can remove NO at a higher conversion rate in exhaust gas containing NO than conventional Cu / ZSM-5. Moreover, since the pore entrance size (hereinafter sometimes referred to as "pore diameter") of the 8-membered ring zeolite is small, it is difficult for hydrocarbons with large molecular sizes contained in exhaust gas to enter the pores, and NO is not competitively adsorbed with hydrocarbons at the catalytic active sites, which is thought to reduce the effect of activity reduction. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a graph showing the evaluation results of the catalytic activity of catalyst 1 (CAT-A) of Example 1 and catalyst 2 (CAT-B) of Comparative Example 1.
[0014] Hereinafter, the embodiments of the present invention will be described in detail. However, the following description is merely an example (representative example) of the embodiment of the present invention, and the present invention is not limited to the contents thereof.
[0015] [Method of purifying nitrogen oxides] The method for purifying nitrogen oxides according to the present invention removes nitrogen oxides contained in a gas by contacting the nitrogen oxides with a zeolite carrying a metal, and is characterized in that the zeolite has an eight-membered ring structure and the molar ratio of the amount of the metal carried to Al contained in the zeolite is 0.5 to 2.0. Here, the gas is preferably an exhaust gas such as an industrial exhaust gas or an automobile exhaust gas.
[0016] <Nitrogen oxides> Nitrogen oxides that can be purified by the catalyst of the present invention include nitric oxide, nitrogen dioxide, nitrous oxide, etc. In this specification, purifying nitrogen oxides means reacting nitrogen oxides on the catalyst and decomposing them into nitrogen, oxygen, etc. In this case, it is preferable to react the nitrogen oxides directly with the catalyst without using a reducing agent, but components that function as reducing agents contained in the actual exhaust gas may coexist. As the reducing agent, ammonia, urea, organic amines, carbon monoxide, hydrocarbons, hydrogen, etc. are used, and ammonia, urea, hydrocarbons, and hydrogen are preferably used.
[0017] <Exhaust purification system> As described above, the nitrogen oxide purification method of the present invention purifies nitrogen oxides contained in exhaust gas, but the exhaust gas may contain components other than nitrogen oxides, such as hydrocarbons, carbon monoxide, carbon dioxide, hydrogen, nitrogen, oxygen, sulfur oxides, and water. Therefore, an exhaust purification system that can purify harmful gases such as hydrocarbons, carbon monoxide, and sulfur oxides at the same time as purifying nitrogen oxides is preferable. In addition, when using a catalyst to purify nitrogen oxides, known reducing agents such as nitrogen-containing compounds (excluding nitrogen oxides) such as ammonia, urea, hydrazine, ammonium carbonate, ammonium carbamate, ammonium hydrogen carbonate, and ammonium formate, and hydrocarbons may be used, but reducing agents that do not contain nitrogen in the molecules that constitute the reducing agent are preferred. Specifically, the exhaust gas treatment catalyst of the present invention can purify nitrogen oxides contained in a wide variety of exhaust gases emitted from diesel automobiles, gasoline automobiles, various diesel engines for stationary power generation, ships, agricultural machinery, construction machinery, motorcycles, and aircraft, boilers, gas turbines, and the like.
[0018] The molar ratio of the reducing agent to the nitrogen oxides contained in the gas with which the catalyst comes into contact is preferably 0.1 or less, more preferably 0.08 or less, even more preferably 0.07 or less, particularly preferably 0.05 or less, particularly preferably 0.03 or less, and most preferably 0.01 or less, with no lower limit being set. In other words, even in the absence of a reducing agent, the catalyst according to the present invention functions effectively and can purify nitrogen oxides. In addition, the ratio of the total molar amount of the nitrogen-containing reducing agent to the total molar amount of the reducing agents contained in the gas with which the catalyst comes into contact is usually 0.1 or less, preferably 0.08 or less, more preferably 0.06 or less, even more preferably 0.05 or less, even more preferably 0.03 or less, and particularly preferably 0.01 or less. As described above, in the present invention, there is no need for a nitrogen-containing reducing agent to be present in the exhaust gas other than the components that function as reducing agents and coexist in the gas.
[0019] In the method of the present invention, it is preferable to purify the exhaust gas by placing a catalyst for purifying nitrogen oxides in the exhaust gas. The method of the present invention may also be used in combination with a known hydrocarbon adsorbent or a known catalyst for removing nitrogen oxides, such as an oxidation catalyst or a three-way catalyst. In this way, an exhaust purification system that combines an adsorbent and a catalyst can effectively remove not only nitrogen oxides from the exhaust gas, but also hydrocarbons, carbon monoxide, and soot.
[0020] When the above-mentioned known adsorbents or catalysts are used in the method of the present invention, the locations of the known adsorbents or catalysts are not particularly limited, and the known adsorbents or catalysts may be installed upstream of the nitrogen oxide purification catalyst, or may be installed downstream of the nitrogen oxide purification catalyst. Also, the known adsorbents may be installed upstream of the nitrogen oxide purification catalyst, and the catalyst may be installed downstream of the nitrogen oxide purification catalyst. The locations of the known adsorbents and catalysts may be determined according to the properties of the materials. As a known adsorbent, for example, an adsorbent that adsorbs nitrogen oxides in a low temperature range where the temperature of the exhaust gas is 200° C. or less, as described in Applied Catalysis A, General 570 (2019) 1-14, may be used.
[0021] There is no particular limitation on the amount of nitrogen oxides contained in the gas to be treated by the method of the present invention, but it is suitably used for treating exhaust gases in which the amount of nitrogen oxides is preferably 10 to 10,000 ppm by volume, more preferably 20 to 5,000 ppm by volume, even more preferably 25 to 4,000 ppm by volume, particularly preferably 50 to 2,000 ppm by volume, and most preferably 100 to 1,000 ppm by volume.
[0022] When a three-way catalyst is used in combination with the method of the present invention, the three-way catalyst is not particularly limited, and may be any catalyst that can be used as a catalyst that can generally treat hydrocarbons (hereinafter sometimes referred to as "HC"), NOx, and CO simultaneously. Preferably, the three-way catalyst is made by supporting a catalytically active component on a refractory inorganic oxide (preferably a porous refractory inorganic oxide). Here, the refractory inorganic oxide is not particularly limited, and a known refractory inorganic oxide can be used. Specifically, examples include those having a high surface area such as activated alumina, silica, zirconia, titania, and ceria, or composite oxides thereof. Among these, activated alumina, zirconia, and ceria are preferred, and activated alumina is particularly preferred. The above refractory inorganic oxides may be used alone or in a mixture of two or more.
[0023] The catalytically active components used in the three-way catalyst include platinum (Pt), rhodium (Rh), palladium (Pd) and mixtures thereof, preferably Pt-Rh, Pd-Rh, Pt-Pd-Rh, more preferably Pd-Rh. In particular, Pt-Rh, Pd-Rh, and Pt-Pd-Rh precious metals supported on porous inorganic oxides are preferably used.
[0024] The three-way catalyst may contain other additive components, such as rare earth metals such as scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), metals such as zirconium (Zr), iron (Fe), cobalt (Co), and nickel (Ni), oxides of the above metals, composite oxides of the above metals, etc. Among these, oxides of Zr, Ce, La, Y, Nd, and Pr, or composite oxides thereof, are preferred, and oxides of Zr, Ce, and La, or composite oxides thereof are more preferred. The three-way catalyst may be used by coating a monolithic carrier, and the monolithic carrier is not particularly limited.
[0025] In the present invention, the monolithic carrier is not particularly limited, and any known carrier can be used. Specifically, the monolithic carrier can be a flow-through type that allows gas to pass through as is, or a filter type that can filter out soot in the exhaust gas.
[0026] Here, when the monolithic carrier is of the flow-through type, the monolithic carrier is also not particularly limited, and known carriers can be used. Specifically, examples include cylindrical monolithic carriers having a large number of through holes penetrating in the axial direction, such as honeycomb, metal honeycomb, plug honeycomb, metal mesh, and corrugated shapes, and foam-type monolithic carriers. Honeycomb-type monolithic carriers and corrugated-type monolithic carriers are preferably used, and honeycomb-type monolithic carriers are particularly preferably used.
[0027] Furthermore, when the monolithic carrier is a honeycomb type or a corrugated type, the monolithic carrier has a plurality of holes, but the structure and manufacturing method are not particularly limited, and structures similar to those known in the art can be used. For example, the monolithic carrier can be manufactured by an extrusion molding method or a method of rolling a sheet-like element. The shape of the gas passage port (cell shape) of the monolithic carrier may be any of hexagonal, tetragonal, triangular, and corrugated shapes. A cell density (cell number / unit cross-sectional area) of 100 to 600 cells / square inch is sufficient for use.
[0028] The material of the monolithic carrier is not particularly limited, and the same material as that usually used can be used. For example, honeycomb carriers made of cordierite, mullite, betalite, alumina (α-alumina), silica, zirconia, titania, titanium phosphate, aluminum titanate, spongimen, aluminosilicate, magnesium silicate, zeolite, silica, etc. are preferable, and cordierite is particularly preferable. In addition, those having an integral structure using oxidation-resistant heat-resistant metals such as stainless steel and Fe-Cr-Al alloys are also used.
[0029] In the case where the monolithic carrier is a filter type, the monolithic carrier has pores in the wall, which can filter out soot and allow gas to pass through the wall. In addition, the filter type includes a carrier in which the holes are sealed in a checkerboard pattern on the exhaust gas inlet side, and the unsealed holes are sealed on the exhaust gas outlet side, and the holes on the exhaust gas outlet side of the sealed holes on the exhaust gas inlet side are not sealed.
[0030] The amount of the three-way catalyst coated (supported) on the monolithic carrier is not particularly limited, and may be the same as the amount of the three-way catalyst coated (supported) known in the art.
[0031] When an oxidation catalyst is used in combination with the method of the present invention, any one that is normally used as an oxidation catalyst capable of oxidizing HC and CO may be used, and a known oxidation catalyst may be used. Preferably, the oxidation catalyst is a catalyst in which a catalytically active component such as a noble metal is supported on a refractory inorganic oxide (preferably a porous refractory inorganic oxide). As the active component, for example, a noble metal such as platinum, palladium, or rhodium is preferable, and as the refractory inorganic oxide, particularly alumina, silica, zirconia, titania, or a composite oxide thereof can be suitably used. More preferably, the catalyst contains a noble metal (catalytically active component) that is platinum and / or palladium, and a refractory inorganic oxide that is alumina, titania, silica, zirconia, or a composite oxide thereof. Furthermore, one or more of rare earth oxides such as lanthanum oxide (La2O3) and metals such as iron, cobalt, and nickel may be added.
[0032] Here, the oxidation catalyst can be used by coating it on a monolithic carrier. In this case, the monolithic carrier is not particularly limited. In addition, the amount of the oxidation catalyst coated (supported) on the monolithic carrier is not particularly limited, and can be the same amount as the amount of the oxidation catalyst coated (supported) on the monolithic carrier.
[0033] In the method of the present invention, exhaust gas containing nitrogen oxides (particularly nitrogen monoxide) is brought into contact with a catalyst to remove nitrogen oxides from the exhaust gas. There are no particular limitations on the conditions for carrying out this treatment, and the treatment can be carried out by appropriately selecting optimal conditions. For example, the space velocity of the exhaust gas (the amount of exhaust gas passing through per catalyst volume in one hour) is approximately 10,000 hr according to the catalytic activity evaluation described in Non-Patent Document 1. -1 However, these conditions are lower than those used when actually treating exhaust gas from automobiles, etc., and since gas does not easily penetrate into the pores of zeolites with small pore sizes, such as the 8-membered ring zeolite used in the catalyst of the present invention, the reaction can be made more efficient under conditions where the boundary film between the catalyst and the gas is made thinner and the gas can more easily come into contact with the catalyst. Therefore, the space velocity is usually 10,000hr -1 More than 15,000 hours, preferably -1More preferably, 20,000 hours -1 More preferably, 30,000 hours or more. -1 More preferably, it is 40,000 hours or more. -1 More preferably, the running time is 50,000 hours or more. -1 More than 60,000 hours is the most preferable. -1 On the other hand, in order to increase the residence time and promote the reaction, it is usually necessary to increase the residence time to 200,000 hours. -1 Less than or equal to 150,000 hours, preferably -1 More preferably, 120,000 hours or less. -1 More preferably, it is 100,000 hours or less. -1 It is particularly preferable that the operating time is 90,000 hours or less. -1 Less than or equal to 80,000 hours, and most preferably -1 The following is the result. Furthermore, in order to increase the reaction rate, the temperature at which exhaust gas containing nitrogen oxides (particularly nitric oxide) is contacted with the catalyst of the present invention is usually 180° C. or higher, preferably 200° C. or higher, more preferably 250° C. or higher, even more preferably 280° C. or higher, and particularly preferably 300° C. or higher. On the other hand, in terms of preventing the catalyst from deteriorating, the temperature is usually 600° C. or lower, preferably 500° C. or lower, more preferably 450° C. or lower, even more preferably 400° C. or lower, and particularly preferably 350° C. or lower.
[0034] [catalyst] The catalyst targeted by the present invention refers to the above-mentioned catalyst capable of purifying nitrogen oxides, specifically, a catalyst for purifying nitrogen oxides that contains a zeolite carrying a metal (hereinafter, sometimes simply referred to as a catalyst).
[0035] [Zeolite] The zeolite used in the present invention refers to zeolites defined by the International Zeolite Association (hereinafter referred to as "IZA"). Specific examples include zeolites containing at least oxygen, aluminum (Al), and phosphorus (P) as atoms constituting the skeletal structure (hereinafter sometimes referred to as "aluminophosphates"), or containing aluminum (Al), silicon (Si), and phosphorus (P) (silicoaluminophosphates), and zeolites containing at least oxygen, aluminum (Al), and silicon (Si) (hereinafter sometimes referred to as "aluminosilicates").
[0036] An aluminosilicate contains at least oxygen, aluminum (Al), and silicon (Si) as atoms that constitute the skeleton structure, and some of these atoms may be substituted with atoms other than P (Me). The other atom Me may be contained in one type or in two or more types. Preferred Me is an element belonging to the third or fourth period of the periodic table.
[0037] As the zeolite of the catalyst according to the present invention, an aluminosilicate is preferred because it has high structural stability in the presence of water vapor. On the other hand, aluminophosphates that have P in the framework are highly hydrophilic and have lower structural stability in the presence of water vapor than aluminosilicates.
[0038] Zeolites are usually crystalline and have a regular network structure in which methane-type SiO4 tetrahedrons or AlO4 tetrahedrons (hereafter, these will be generalized as TO4, and the atoms other than oxygen contained therein will be called T atoms) are connected by sharing the oxygen atoms at each vertex. Atoms other than Al and Si are also known as T atoms. One of the basic units of the network structure is eight TO4 tetrahedrons connected in a ring, which is called an eight-membered ring. Similarly, six-membered rings and ten-membered rings are also basic units of the zeolite structure.
[0039] The structure of the zeolite used in the present invention is determined by X-ray diffraction (hereinafter referred to as "XRD").
[0040] The zeolite used in the present invention is preferably a zeolite having an eight-membered ring structure in the framework structure, with the largest pore in the zeolite crystal structure being formed by the eight-membered oxygen ring. Specific examples of zeolites with an 8-membered ring structure include the following codes set by IZA: ABW, AEI, AEN, AFN, AFR, AFS, AFT, AFX, AFY, ANA, APC, APD, ATN, ATT, ATV, AWO, AWW, BCT, BIK, BPH, BRE, CAS, CDO, CGF, CGS, CHA, CLO, DAC, DDR, DFO, DFT, EAB, EDI, EON, EPI, ERI, ESV, ETR, FER, GIS, GME, GOO, HEU, IHW, ITE, ITW, IWW, JBW, KFI, LAW, LEV, LOV, and LTA. , MAZ, MER, MFS, MON, MOR, MOZ, MTF, NAT, NSI, OBW, OFF, OSO, OWE, PAU, PHI, RHO, RRO, RSN, RTE, RTH, RWR, SAS, SAT, SAV, SBE, SFO, SIV, SOS, STI, SZR, THO, TSC, UEI, UFI, VNI, VSV, WEI, WEN, YUG, ZON, and MWF can be mentioned, but among them, from the viewpoint of catalytic activity, it is preferable to use any one selected from AEI, CHA, AFX, and RHO, with AEI and CHA being particularly preferable, and AEI being most preferable.
[0041] AEI zeolite is a code that specifies the zeolite framework structure defined by IZA, and is an AEI structure. The structure is characterized by X-ray diffraction data. However, when measuring an actual zeolite, the intensity ratio and peak position of each peak may vary slightly due to the influence of the zeolite growth direction, the ratio of constituent elements, adsorbed substances, the presence of defects, the drying state, etc., so the values obtained are not exactly the same as the parameters of the AEI structure specified by IZA, and a margin of about 10% is allowed. For example, when CuKα radiation is used as the radiation source, major peaks in X-ray diffraction include the 110 plane peak at 2θ=9.5°±0.2°, the 202 peak at 2θ=16.1°±0.2° (which are very close and often overlap), the 022 plane peak at 16.9°±0.2°, and the 310 plane peak at 20.8°±0.2°.
[0042] More preferred zeolites for use in the present invention are aluminosilicates, and are zeolites in which the largest pore in the zeolite crystal structure has an eight-membered ring structure. The zeolites of the present invention may contain cations that can be ion-exchanged with other cations, in addition to the components that constitute the framework structure as the basic unit. In this case, the cations are not particularly limited, but include protons, alkali elements such as Li, Na, K, and Cs, alkaline earth elements such as Mg and Ca, and rare earth elements such as La and Ce, and among these, protons, alkali elements, and alkaline earth elements are preferred.
[0043] The framework density of the zeolite in the present invention (hereinafter sometimes abbreviated as "FD") is not particularly limited, but is usually 13.0 T / nm 3 More than 13.5T / nm, preferably 3 More preferably, 14.0 T / nm 3 That's it. On the other hand, normally 17.5T / nm 3 Less than or equal to 17.0T / nm 3 Less than or equal to 16.5T / nm 3 or less, more preferably 16.0 T / nm 3 or less, and particularly preferably 15.5 T / nm 3 or less, most preferably 15.0 T / nm 3 The framework density (T / nm 3 ) is the unit volume of zeolite nm 3It means the number of T atoms (atoms of elements other than oxygen that constitute the framework of zeolite) present per unit area, and this value is determined by the structure of the zeolite. When the FD is high, the structure tends to be stable and sufficient durability is obtained, while when the FD is low, sufficient adsorption amount and catalytic activity are obtained, making it suitable for use as a catalyst. The above framework density is the value described in ATLAS OF ZEOLITE FRAME WORK TYPES (Sixth Revised Edition, 2007, ELSEVIER) by Ch. Baerlocher et al.
[0044] The maximum pore size in the crystal structure of the zeolite used in the present invention is not particularly limited, but a small pore size is preferable in order to prevent the diffusion of nitrogen oxides from being hindered by the intrusion of hydrocarbons and the like contained in exhaust gas into the pores, and therefore the pore size is usually 5.0 Å or less, preferably 4.5 Å or less, more preferably 4.3 Å or less, even more preferably 4.2 Å or less, particularly preferably 4.1 Å or less, particularly preferably 4.0 Å or less, and most preferably 3.8 Å or less. On the other hand, from the viewpoint of gas diffusion, it is preferable that the pore diameter is large. Therefore, it is usually 3.0 Å or more, preferably 3.2 Å or more, more preferably 3.4 Å or more, particularly preferably 3.5 Å or more, and most preferably 3.6 Å or more. The above pore diameter is the value described in ATLAS OF ZEOLITE FRAME WORK TYPES (Sixth Revised Edition, 2007, ELSEVIER) by Ch. Baerlocher et al.
[0045] The zeolite used in the present invention can be obtained by changing the composition ratio of the raw materials in the zeolite manufacturing method described later. In addition, when AEI zeolite is used, AEI zeolite with a wide range of SiO2 / Al2O3 molar ratios can be produced by changing the composition ratio of the raw materials in the AEI zeolite manufacturing method described later. Therefore, the SiO2 / Al2O3 molar ratio of the zeolite used in the present invention is not particularly limited. However, since it is preferable to have more active sites as a catalyst, the SiO2 / Al2O3 molar ratio is usually 100 or less, preferably 50 or less, more preferably 40 or less, even more preferably 30 or less, particularly preferably 25 or less, particularly preferably 22 or less, and most preferably 20 or less. On the other hand, when a zeolite having a large amount of Al in the framework is exposed to a gas containing water vapor, there is a high possibility that Al in the framework will be released and the structure will be destroyed, so the SiO2 / Al2O3 molar ratio is usually 3 or more, preferably 5 or more, more preferably 8 or more, even more preferably 10 or more, particularly preferably 12 or more, and most preferably 15 or more. That is, the SiO2 / Al2O3 molar ratio of the zeolite used in the present invention is preferably 3 to 100.
[0046] The nitrogen oxide purification catalyst preferably purifies exhaust gas containing nitrogen oxides and has hydrothermal durability of 650°C or more. If there is no difference in crystallinity, zeolites with a low SiO2 / Al2O3 molar ratio have more active sites than catalysts with a high SiO2 / Al2O3 molar ratio, and therefore exhibit high purification performance for exhaust gas containing nitrogen oxides. For example, in trucks, catalysts are usually used at relatively low temperatures of 700°C or less and in a gas atmosphere containing water vapor, so that dealuminization of Al in the framework by water vapor does not proceed easily. Therefore, the purification performance of exhaust gas containing nitrogen oxides is prioritized, and it is desired to use zeolites with a SiO2 / Al2O3 molar ratio of usually 100 or less, preferably 50 or less, more preferably 25 or less, and most preferably 22 or less, which have many active sites in the zeolite framework. On the other hand, zeolites with a high SiO2 / Al2O3 molar ratio have the advantage that the structure is less likely to collapse even in a high-temperature gas atmosphere containing water vapor, since the amount of Al in the zeolite framework is small. In diesel passenger cars and gasoline vehicles, high water vapor resistance is required because the catalyst is usually used in a gas atmosphere containing water vapor at 800°C or higher. Therefore, it is desirable to use a zeolite with a SiO2 / Al2O3 molar ratio of more than 5, more preferably 10 or more, even more preferably 12 or more, and particularly preferably 15 or more.
[0047] The zeolite used in the present invention usually has an acid amount of 0.3 mmol / g or more, preferably 0.6 mmol / g or more, more preferably 0.8 mmol / g or more, even more preferably 1.0 mmol / g or more, particularly preferably 1.2 mmol / g or more, and preferably 3.0 mmol / g or less, more preferably 2.5 mmol / g or less, and even more preferably 2.0 mmol / g or less.
[0048] The average primary particle size of the zeolite used in the present invention is not particularly limited, but is preferably 0.01 to 10 μm, more preferably 0.02 to 8 μm, and even more preferably 0.05 to 5 μm in order to improve gas diffusivity when used as a catalyst. In particular, the average primary particle size of the zeolite used in the present invention is preferably 0.01 μm or more and 3 μm or less, and is preferably in the range of 0.1 to 3 μm in terms of ease of handling. Specifically, the average primary particle diameter of the zeolite can be measured by the method described in the Examples section below.
[0049] The specific surface area of the zeolite used in the present invention is not particularly limited. However, since there are many active sites present on the inner surface of the pores, it is preferably 300 to 1000 m 2 / g, more preferably 350 to 800 m 2 / g, and even more preferably 450 to 750 m 2 / g. The specific surface area of the zeolite can be measured by the BET method.
[0050] <Method for Producing Zeolite> Known compounds can be used as the zeolite used in the present invention. Also, the zeolite used in the present invention can be produced according to a commonly used method. The method for producing the zeolite in the present invention is not particularly limited. For example, when using AEI-type zeolite, it can be produced according to the methods described in U.S. Patent No. 5,958,370, International Publication No. WO 2015 / 005369, and Japanese Unexamined Patent Application Publication No. 2017-81809. Hereinafter, taking the AEI-type zeolite, which is particularly preferable as the zeolite used in the present invention, as a representative example, the AEI-type zeolite and its production method will be described in detail.
[0051] <Method for Producing AEI-Type Zeolite> <Aluminum Atom Raw Material> The aluminum atom raw material used in producing the AEI zeolite used in the present invention is not particularly limited. Therefore, crystalline aluminosilicate zeolite or amorphous aluminosilicate may be used, but preferably, an aluminum source that does not substantially contain Si except for that mixed as an impurity during the production process is preferable, and amorphous aluminum hydroxide, aluminum hydroxide having a gibbsite structure, aluminum hydroxide having a Bayerite structure, aluminum nitrate, aluminum sulfate, aluminum oxide, sodium aluminate, boehmite, pseudo-boehmite, and aluminum alkoxide are preferable. Particularly preferable are amorphous aluminum hydroxide, aluminum hydroxide having a gibbsite structure, and aluminum hydroxide having a Bayerite structure, and among these, amorphous aluminum hydroxide is particularly preferable. These may be used alone or in combination of two or more. These raw materials are easily available in stable quality, and cost reduction can be achieved.
[0052] The amount of the aluminum atom raw material used, in terms of ease of preparation of the pre-reaction mixture or the aqueous gel obtained by aging the pre-reaction mixture and production efficiency, is usually 100 or less, preferably 80 or less, more preferably 60 or less, even more preferably 50 or less, and particularly preferably 40 or less, in terms of the molar ratio of silicon (converted into SiO2) to aluminum (converted into Al2O3) in the aluminum atom raw material contained in the raw material mixture other than the zeolite added in the present invention. In addition, the lower limit is not particularly limited, but in terms of ease of uniformly dissolving the aluminum atom raw material in the aqueous gel, it is usually 5 or more, preferably 10 or more, more preferably 15 or more, even more preferably 20 or more, particularly preferably 25 or more, and most preferably 30 or more.
[0053] <Silicon atom raw material> The silicon atom raw material used in producing the AEI zeolite used in the present invention is not particularly limited, and various known substances can be used, for example, crystalline aluminosilicate zeolite or amorphous aluminosilicate can be used. Preferably, an aluminum source that does not substantially contain Al except for that mixed in as an impurity during the production process is good, and colloidal silica, amorphous silica, sodium silicate, trimethylethoxysilane, tetraethylorthosilicate, etc. can be used. These may be used alone or in combination of two or more. Among these, materials that can be mixed sufficiently uniformly with other components and are particularly easily soluble in water are preferred, with colloidal silica, trimethylethoxysilane, and tetraethylorthosilicate being preferred, and colloidal silica being most preferred. The silicon atom source is used so that the ratio of the amount of the other source to the amount of the silicon atom source falls within the preferred ranges described above or below.
[0054] <Alkali metal atom source> The alkali metal contained in the alkali metal atom raw material used in producing the AEI zeolite used in the present invention is not particularly limited, and any known alkali metal atom raw material used in the synthesis of zeolites can be used, but it is preferable that the alkali metal contains at least one alkali metal ion selected from the group consisting of lithium, sodium, potassium, rubidium, and cesium. By containing these alkali metal atoms, crystallization proceeds more easily and by-products (impurity crystals) are less likely to be produced.
[0055] As the alkali metal atom source, inorganic acid salts such as hydroxides, oxides, sulfates, nitrates, phosphates, chlorides, bromides, etc., and organic acid salts such as acetates, oxalates, citrates, etc., of the above-mentioned alkali metal atoms can be used. One or more kinds of alkali metal atom sources may be contained.
[0056] By using an appropriate amount of alkali metal atom raw material, the alkali metal atoms necessary for charge compensation in the crystal structure can be suitably coordinated to aluminum, making it easier to create a crystal structure. The molar ratio of alkali metal atoms to silicon (Si) contained in the raw material mixture other than the zeolite added in the present invention in the raw material mixture is usually 0.05 or more, preferably 0.10 or more, more preferably 0.15 or more, even more preferably 0.20 or more, particularly preferably 0.25 or more, particularly preferably 0.30 or more, and most preferably 0.35 or more. On the other hand, the amount of alkali metal atoms is preferably small so that the coordination of the organic structure-directing agent to aluminum is less likely to be hindered by the alkali metal atoms, and is usually preferably 1.0 or less, more preferably 0.80 or less, even more preferably 0.60 or less, particularly preferably 0.50 or less, particularly preferably 0.45 or less, and most preferably 0.40 or less.
[0057] <Organic structure directing agent> As the organic structure directing agent (also called "template." Hereinafter, the organic structure directing agent may be referred to as "SDA."), various known substances such as tetraethylammonium hydroxide (TEAOH) and tetrapropylammonium hydroxide (TPAOH) can be used. In addition, for example, as the nitrogen-containing organic structure directing agent described in U.S. Pat. No. 5,958,370, the following substances can be used.
[0058] That is, N,N-diethyl-2,6-dimethylpiperidinium cation, N,N-dimethyl-9-azoniabicyclo[3.3.1]nonane, N,N-dimethyl-2,6-dimethylpiperidinium cation, N-ethyl-N-methyl-2,6-dimethylpiperidinium cation, N,N-diethyl-2-ethylpiperidinium cation, N,N-dimethyl-2-(2-hydroxyethyl)piperidinium cation, N,N-dimethyl-2-ethylpiperidinium cation, N,N-dimethyl-3,5-dimethylpiperidinium cation, N-ethyl-N-methyl-2-ethylpiperidinium cation, 2,6-dimethyl-1-azonium[5.4]decane cation, N-ethyl-N-propyl-2,6-dimethylpiperidinium cation, etc. In addition, when there are structural isomers such as cis isomers and trans isomers, any of them may be used, and a mixture of cis isomers and trans isomers may be used. Among these, a particularly preferred nitrogen-containing organic structure-directing agent is N,N-dimethyl-3,5-dimethylpiperidinium cation, and specifically, it is preferable to use N,N-dimethyl-3,5-dimethylpiperidinium hydroxide.
[0059] In addition, as a phosphorus-containing organic structure-directing agent, substances such as tetrabutylphosphonium and diphenyldimethylphosphonium described in Chemistry Letters (2014), Vol. 43, No. 3, pp. 302-304, can be used. However, since phosphorus compounds may generate the harmful substance diphosphorus pentaoxide when the synthesized zeolite is calcined to remove SDA, nitrogen-containing organic structure directing agents are preferred.
[0060] These organic structure-directing agents may be used alone or in combination of two or more.
[0061] The amount of the organic structure directing agent used is, from the viewpoint of ease of crystal formation, usually 0.01 or more, preferably 0.05 or more, more preferably 0.1 or more, even more preferably 0.15 or more, and particularly preferably 0.2 or more, in terms of the molar ratio to silicon (Si) contained in the raw material mixture other than the zeolite used in the present invention. Also, from the viewpoint of cost reduction, it is usually 1.0 or less, preferably 0.8 or less, more preferably 0.6 or less, even more preferably 0.5 or less, particularly preferably 0.4 or less, particularly preferably 0.3 or less, and most preferably 0.25 or less.
[0062] In addition, a quaternary ammonium cation may be mixed into the raw material composition. Specific examples of the quaternary ammonium cation include tetramethylammonium cation, ethyltrimethylammonium cation, trimethylpropylammonium cation, isopropyltrimethylammonium cation, butyltrimethylammonium cation, isobutyltrimethylammonium cation, secondary butyltrimethylammonium cation, tertiary butyltrimethylammonium cation, hydroxymethyltrimethylammonium cation, dihydroxymethyltrimethylammonium cation, trihydroxymethyltrimethylammonium cation, (2-hydroxyethyl)trimethylammonium cation, (1-hydroxyethyl)trimethylammonium cation, (1-hydroxypropyl)trimethylammonium cation, (2-hydroxypropyl)trimethylammonium cation, (3-hydroxypropyl)trimethylammonium cation, (2-hydroxy-1-methylethyl)trimethylammonium cation, (1-hydroxy-1-methylethyl)trimethylammonium cation, (2, ...1-hydroxy-1-methylethyl)trimethylammonium cation, (1-hydroxy-1-methylethyl)trimethylammonium cation, (1-hydroxy-1-methylethyl)trimethylammonium cation, (1-hydroxy-1-methylethyl)trimethylammonium cation, (1-hydroxy-1-methylethyl)trimethylammonium cation, (1-hydroxy-1-methylethyl)trimethylammonium cation, (1-hydroxy-1-methyl (dihydroxypropyl)trimethylammonium cation, (1-hydroxybutyl)trimethylammonium cation, (2-hydroxybutyl)trimethylammonium cation, (3-hydroxybutyl)trimethylammonium cation, (4-hydroxybutyl)trimethylammonium cation, (1-hydroxy-2-methylpropyl)trimethylammonium cation, (2-hydroxy-2-methylpropyl)trimethylammonium cation, (3-hydroxy-2-methylpropyl)trimethylammonium cation, (1-hydroxy-1-methylpropyl)trimethylammonium cation, (2-hydroxy-1-methylpropyl)trimethylammonium cation, (3-hydroxy-1-methylpropyl)trimethylammonium cation, (2-aminoethyl)trimethylammonium cation, (2-mercaptoethyl)trimethylammonium cation, (2-chloroethyl)trimethylammonium cation, (2-oxoethyl)trimethylammonium cation, (3-aminopropyl)trimethylammonium cationat least one selected from the group consisting of (2-methoxyethyl)trimethylammonium cation, (2-oxopropyl)trimethylammonium cation, (4-oxobutyl)trimethylammonium cation, (2-amino-2-oxoethyl)trimethylammonium cation, (2-carboxyethyl)trimethylammonium cation, (2-hydroxyiminoethyl)trimethylammonium cation, and (3-chloro-2-hydroxypropyl)trimethylammonium cation, further including tetramethylammonium cation (hereinafter also referred to as "TMA"), ethyltrimethylammonium cation (hereinafter also referred to as "ETMA"), trimethylpropylammonium cation (hereinafter also referred to as "TMPA"), isopropyl trimethylammonium cation (hereinafter also referred to as "IPTMA"), butyltrimethylammonium cation (hereinafter also referred to as "BTMA"), isobutyltrimethylammonium cation (hereinafter also referred to as "IBTMA"), secondary butyltrimethylammonium cation (hereinafter also referred to as "SIBTMA"), hydroxymethyltrimethylammonium cation (hereinafter also referred to as "HMTMA"), (2-hydroxyethyl)trimethylammonium cation (hereinafter also referred to as "2-HETMA"), (2-hydroxypropyl)trimethylammonium cation (hereinafter also referred to as "2-HPTMA"), and (2-hydroxybutyl)trimethylammonium cation (hereinafter also referred to as "2-HPTMA").
[0063] The amount of the quaternary ammonium cation used is preferably 0.0001 or more and 0.1 or less, more preferably 0.001 or more and 0.05 or less, and even more preferably 0.001 or more and 0.01 or less, in terms of a molar ratio to silicon (Si) contained in the raw material mixture. By setting the amount within this range, the crystallization of the AEI zeolite is easily promoted.
[0064] <Water> From the viewpoint of facilitating crystal formation, the amount of water used, in terms of a molar ratio to silicon (Si) contained in the raw material mixture other than the zeolite used in the present invention, is usually 5 or more, preferably 7 or more, more preferably 9 or more, even more preferably 10 or more, and particularly preferably 12 or more. On the other hand, from the viewpoint of reducing costs for waste liquid treatment, the amount of water used, in terms of a molar ratio to silicon (Si) contained in the raw material mixture other than the zeolite used in the present invention, is usually 100 or less, preferably 50 or less, more preferably 40 or less, even more preferably 30 or less, particularly preferably 25 or less, particularly preferably 20 or less, and most preferably 15 or less.
[0065] <Mixing of raw materials (preparation of pre-reaction mixture)> In the method for producing the AEI zeolite used in the present invention, the aluminum atom raw material, the silicon atom raw material, the alkali metal atom raw material, the organic structure directing agent, and water are mixed together as described above. Here, zeolite may be added as seed crystals to this mixture and mixed thoroughly, and then the resulting pre-reaction mixture may be subjected to hydrothermal synthesis.
[0066] Zeolites used as seed crystals are preferably those having a double 8 ring (hereinafter referred to as "D8r") in the composition building unit (hereinafter referred to as "CBU") contained in the zeolite crystal structure, and specific examples thereof include AEI, AFT, AFX, CHA, EAB, EMT, ERI, FAU, GME, KFI, LEV, LTL, LTN, MOZ, MSO, MWW, OFF, SAS, SAT, SAV, SBS, SBT, SZR, TSC, and WEN. Among these, AEI, AFX, and CHA are more preferable, and AEI and CHA are particularly preferable.
[0067] The order of mixing these raw materials is not particularly limited, but since the raw materials are more easily dissolved uniformly when the silicon atom source and the aluminum atom source are added after the alkaline solution is prepared, it is preferable to prepare an alkaline solution by mixing water, an organic structure-directing agent, and an alkali metal atom source, and then add and mix the aluminum atom source, silicon atom source, and seed crystal zeolite to this alkaline solution in this order.
[0068] In the method for producing the AEI zeolite used in the present invention, in addition to the above-mentioned aluminum atom raw material, silicon atom raw material, alkali metal atom raw material, organic structure-directing agent, water, and zeolite as seed crystals, auxiliary agents that serve as components for assisting the synthesis of zeolite, for example, acid components that promote the reaction, and other additives such as metal stabilizers such as polyamines, may be added and mixed in any step as necessary to prepare a pre-reaction mixture, and a metal such as copper that acts as a catalyst as described below may be added during the hydrothermal synthesis.
[0069] <Addition of alkaline earth metals> In addition, an alkaline earth metal can be added during the synthesis of zeolite. Adding an alkaline earth metal can improve the hydrothermal resistance of zeolite. When producing the AEI zeolite used in the method of the present invention, a compound containing an alkaline earth metal can be added to the raw material mixture before hydrothermal synthesis. As the alkaline earth metal, magnesium, calcium, strontium, barium, etc. can be used, preferably magnesium or calcium, and most preferably calcium. The alkaline earth metal can be supplied in the form of a compound, such as an oxide, hydroxide, sulfide, etc. Any of these supply forms can be used and are not particularly limited, but it is preferable to add it in the form of a hydroxide.
[0070] <Aging> The pre-reaction mixture prepared as described above may be hydrothermally synthesized immediately after preparation, but in order to obtain a zeolite with higher crystallinity, it is preferable to age it for a certain period of time under a predetermined temperature condition. In particular, when scaling up, it becomes difficult to stir uniformly, and the raw material tends to be insufficiently mixed. Therefore, it is preferable to improve the raw material to a more uniform state by aging the raw material while stirring it for a certain period of time. The aging temperature is usually 100°C or less, preferably 95°C or less, more preferably 90°C or less, and particularly preferably 80°C or less, and the lower limit is not particularly limited, but is usually 0°C or more, preferably 20°C or more, more preferably 30°C or more, even more preferably 40°C or more, and particularly preferably 50°C or more. The aging temperature may be constant during aging, or may be changed stepwise or continuously. The aging period is not particularly limited, but is usually 2 hours or more, preferably 3 hours or more, more preferably 5 hours or more, and is usually 30 days or less, preferably 10 days or less, and more preferably 4 days or less.
[0071] <Hydrothermal synthesis> Hydrothermal synthesis is carried out by placing the pre-reaction mixture prepared as described above or an aqueous gel obtained by maturing the pre-reaction mixture in a pressure-resistant container, and maintaining the mixture at a predetermined temperature under self-generated pressure or under gas pressure to an extent that does not inhibit crystallization, while stirring, rotating or rocking the container, or leaving the mixture stationary.
[0072] The reaction temperature during hydrothermal synthesis is usually 120°C or higher, preferably 130°C or higher, more preferably 140°C or higher, even more preferably 150°C or higher, particularly preferably 160°C or higher, and most preferably 170°C or higher, and on the other hand, usually 230°C or lower, preferably 220°C or lower, more preferably 200°C or lower, even more preferably 190°C or lower, and particularly preferably 180°C or lower. The reaction time is not particularly limited, but is usually 5 hours or more, preferably 10 hours or more, more preferably 1 day or more, even more preferably 1.5 days or more, even more preferably 2 days or more, and particularly preferably 3 days or more, and on the other hand, usually 30 days or less, preferably 10 days or less, more preferably 7 days or less, and even more preferably 5 days or less. The reaction temperature may be constant during the reaction, or may be changed stepwise or continuously. By carrying out the reaction under the above conditions, the yield of the target AEI zeolite is improved and it is difficult to produce a different type of zeolite, which is preferable.
[0073] <Zeolite Recovery> After the above hydrothermal synthesis, the product zeolite is separated from the hydrothermal synthesis reaction liquid. The obtained zeolite (hereinafter referred to as "SDA etc.-containing zeolite") contains both or either of an organic structure directing agent and an alkali metal atom in the pores. The method for separating the SDA etc.-containing zeolite from the hydrothermal synthesis reaction liquid is not particularly limited, but typically includes methods such as filtration, decantation, or direct drying.
[0074] The SDA-containing zeolite separated and recovered from the hydrothermal synthesis reaction liquid can be washed with water and dried as necessary to remove the organic structure-directing agent, etc. used during production, and then calcined or otherwise treated to obtain a zeolite that does not contain the organic structure-directing agent, etc. When the zeolite used in the present invention is used as a catalyst (including a catalyst support) or an adsorbent, these may be removed as necessary before use.
[0075] <Recycling of separated liquid containing organic structure directing agent> After separating and recovering zeolite from the hydrothermal synthesis reaction solution, the separated solution obtained contains unreacted structure-directing agent. Using the separated solution containing the unreacted structure-directing agent, silicon atom raw material, aluminum atom raw material, organic structure-directing agent, water, etc. that are insufficient are added to make the same charging composition as the gel before hydrothermal synthesis, and a mixture is prepared. By subjecting this mixture to hydrothermal synthesis, the unreacted structure-directing agent in the separated solution may be reused. Also, due to the influence of trace components contained in the recovered filtrate, even with the same charging composition, zeolite may not crystalize or may form a mixed phase containing impurities. In that case, the charging composition and hydrothermal synthesis conditions may be adjusted so that zeolite can be obtained as a single phase even when using the filtrate. As a specific method for recycling the unreacted structure-directing agent, for example, the methods described in U.S. Patent Publication No. 2015 / 0118150 or Japanese Patent Laid-Open Publication No. 2019-202929 may be used.
[0076] <Removal of Organic Structure-Directing Agent, etc. from Zeolite Containing SDA, etc.> For the removal treatment of both or either one of the organic structure-directing agent and the alkali metal from zeolite containing SDA, etc., a liquid phase treatment using an acidic solution or a chemical solution containing a decomposition component of the organic structure-directing agent, an ion exchange treatment using a resin, etc., or a thermal decomposition treatment can be employed, and these treatments may be used in combination. Usually, the contained organic structure-directing agent, etc. can be removed by methods such as firing at a temperature of 300°C to 1000°C in air, an oxygen-containing inert gas, or an inert gas atmosphere, or extraction with an organic solvent such as an aqueous ethanol solution. From the viewpoint of productivity, removal of the organic structure-directing agent, etc. by firing is preferred. In this case, regarding the firing temperature, it is preferably 400°C or higher, more preferably 450°C or higher, still more preferably 500°C or higher, and on the other hand, it is preferably 900°C or lower, more preferably 850°C or lower, still more preferably 800°C or lower. As the inert gas, nitrogen, etc. can be used.
[0077] The ion exchange capacity of the zeolite used in the present invention is achieved by converting the alkali metal atom source, or the alkali metal portion derived from the alkali metal atom contained in the alkali metal atom source, the aluminum atom source, the silicon atom source, the organic structure directing agent, and the seed crystal zeolite into a proton type or an NH4 + It is also possible to use the compound by converting it into the above-mentioned form. This can be done by using a known technique. For example, this can be done by treating it with an ammonium salt such as NH4NO3 or NaNO3 or an acid such as hydrochloric acid at a temperature between room temperature and 100°C, followed by washing with water.
[0078] <Improved heat resistance through post-loading of metal> The zeolite used in the present invention may further support a metal on the catalyst after supporting a metal (e.g., Cu or Fe) that serves as an active site in order to be used as a catalyst described later. It is considered that the effect of supporting a metal is that the metal coordinates with Al in the zeolite framework, thereby exerting a protective effect against water vapor. Examples of the metal to be supported include Mg, Ca, Sr, La, Pr, B, Zr, and Ce. Two or more of these metals may be used in combination. In addition, a salt of these metals may be added to the gel before the hydrothermal synthesis of the AEI zeolite to produce a zeolite containing a metal. In this case, inorganic acid salts such as sulfates, phosphates, nitrates, chlorides, and bromides of transition metals, organic acid salts such as acetates, oxalates, and citrates, and organometallic compounds such as pentacarbonyl and ferrocene are usually used. Among these salts, inorganic acid salts and organic acid salts are preferred from the viewpoint of solubility in water.
[0079] When the above-mentioned metals are supported on the zeolite, the content of the metal in the metal-supported zeolite is usually 0.0001 or more, preferably 0.0005 or more, more preferably 0.001 or more, and even more preferably 0.005 or more, expressed as a molar ratio of the metal to the aluminum in the zeolite. The upper limit of the metal content is not particularly limited, but when used as a catalyst, the transition metal that serves as the active site must also be ion-exchanged, so that the upper limit is usually 1 or less, preferably 0.95 or less, more preferably 0.8 or less, and even more preferably 0.5 or less.
[0080] [Nitrogen oxide purification catalyst] When using zeolite as a catalyst, it can be mixed with a binder and granulated or molded into a predetermined shape such as a honeycomb. When using the catalyst for exhaust gas treatment, in particular, the catalyst can be mixed with an inorganic binder such as silica, alumina, or clay mineral, or an inorganic fiber such as alumina fiber or glass fiber, and then granulated or molded into a predetermined shape such as a honeycomb by an extrusion method or a compression method, followed by firing to obtain a granular catalyst, honeycomb catalyst, or molded catalyst product.
[0081] When using zeolite as a catalyst, it may be applied to a substrate such as a sheet or honeycomb. Specifically, for example, a method may be used in which a catalyst containing the zeolite used in the present invention is mixed with an inorganic binder such as silica, alumina, or clay mineral to prepare a slurry, which is then applied to the surface of a substrate made of an inorganic material such as cordierite, and then fired. Preferably, the catalyst is applied to a substrate having a honeycomb shape, thereby obtaining a honeycomb-shaped honeycomb catalyst coated with the catalyst.
[0082] In this example, an inorganic binder is used because an exhaust gas treatment catalyst is used as an example, but it goes without saying that an organic binder may be used depending on the application and conditions of use.
[0083] When using zeolite as a catalyst, a metal is supported on the zeolite. The supported metal is a metal other than Si and Al. The metal supported on the zeolite is preferably a transition metal, and is preferably iron, cobalt, palladium, iridium, platinum, copper, silver, gold, cerium, lanthanum, praseodymium, titanium, zirconium, or the like. More preferably, it is copper or iron, and most preferably, it is copper. Two or more of these metals may be combined. The amount of the metal supported is usually 1.0 mass% or more, preferably 2.0 mass% or more, more preferably 3.0 mass% or more, even more preferably 5.0 mass% or more, particularly preferably 6.0 mass% or more, particularly preferably 8.0 mass% or more, and most preferably 10 mass% or more, based on the total amount of the catalyst, and on the other hand, it is usually 20 mass% or less, preferably 18 mass% or less, more preferably 15 mass% or less, even more preferably 12 mass% or less, and particularly preferably 10 mass% or less. That is, the amount of the metal supported on the zeolite is preferably 1.0 to 20 mass% based on the total amount of the catalyst.
[0084] The molar ratio of the amount of metal supported to Al in the zeolite is usually 0.5 or more, preferably 0.55 or more, more preferably 0.6 or more, even more preferably 0.65 or more, particularly preferably 0.7 or more, particularly preferably 0.75 or more, and most preferably 0.8 or more. The upper limit is usually 2.0 or less, preferably 1.95 or less, more preferably 1.9 or less, even more preferably 1.85 or less, and particularly preferably 1.8 or less. That is, the amount of metal supported on the zeolite is preferably 0.5 to 2.0 as a molar ratio to Al in the zeolite.
[0085] <Method of manufacturing metal-supported catalyst> The method for supporting a metal on a zeolite is not particularly limited, but examples thereof include commonly used ion exchange methods, impregnation support methods, precipitation support methods, solid-phase ion exchange methods, CVD methods, spray drying methods, and the like. Among these, the methods for supporting a metal on an AEI zeolite by the solid-phase ion exchange methods, impregnation support methods, and spray drying methods are preferred, and the impregnation support method is most preferred.
[0086] When a metal is supported on a zeolite by the impregnation support method, the treatment may be performed by vacuum distillation. The temperature of the aqueous solution containing the zeolite and the supported metal raw material when performing vacuum distillation is usually 0° C. or higher, preferably 20° C. or higher, more preferably 30° C. or higher, even more preferably 40° C. or higher, and particularly preferably 50° C. or higher. On the other hand, the upper limit is usually 100° C. or lower, preferably 90° C. or lower, more preferably 80° C. or lower, even more preferably 70° C. or lower, and particularly preferably 60° C. or lower.
[0087] The concentration of the metal raw material in the aqueous solution when impregnating and supporting is not particularly limited, but in order to efficiently impregnate and support, the higher the concentration, the better, and it is usually 0.1 mass%, preferably 0.3 mass% or more, more preferably 0.5 mass% or more, even more preferably 0.8 mass% or more, particularly preferably 1.0 mass% or more, especially preferably 1.2 mass% or more, and most preferably 1.5 mass% or more. On the other hand, since the dispersibility when supporting the metal on the zeolite is easily improved, it is usually 10 mass% or less, preferably 8 mass% or less, more preferably 6 mass% or less, more preferably 5 mass% or less, especially preferably 3 mass% or less, and especially preferably 2 mass% or less.
[0088] When a transition metal is supported on a zeolite, if a method such as an ion exchange method or an impregnation method is used, a large amount of waste liquid is discharged, which makes waste liquid treatment a problem, and the number of steps such as filtration and washing of the zeolite immersion slurry tends to increase. In contrast, this problem can be solved by a one-pot synthesis method in which an AEI type zeolite containing a transition metal is synthesized in one step by introducing a transition metal oxide or transition metal salt, which is a transition metal raw material, into the gel of the zeolite synthesis process, i.e., the above-mentioned pre-reaction mixture.
[0089] The transition metal raw material used in the one-pot synthesis method is not particularly limited, and typically includes inorganic acid salts such as sulfates, phosphates, nitrates, chlorides, and bromides of transition metals, organic acid salts such as acetates, oxalates, and citrates, and organometallic compounds such as pentacarbonyl and ferrocene. Among these, inorganic acid salts and organic acid salts are preferred from the viewpoint of solubility in water, and more specifically, for example, nitrates, sulfates, acetates, and hydrochlorides are preferred. In some cases, colloidal oxides or fine powder oxides may be used.
[0090] In order to stabilize the transition metal in the gel, a complex salt may be formed using a polyamine. As specific polyamines, diethylenetriamine, triethylenetetramine, and tetraethylenepentamine are inexpensive and preferable, and triethylenetetramine and tetraethylenepentamine are particularly preferable. These polyamines may be used alone or in combination of two or more. Also, branched polyamines may be included.
[0091] After the metal is supported on the zeolite, it is preferable to calcinate the zeolite for about 1 second to 24 hours, preferably for 10 seconds to 8 hours, and more preferably for 30 minutes to 5 hours, at preferably 300° C. to 900° C., more preferably 350° C. to 850° C., and even more preferably 400° C. to 800° C. Although this calcination is not necessarily required, calcination can increase the dispersibility of the metal supported on the zeolite framework structure, and is effective in improving the catalytic activity.
[0092] The catalyst used in the present invention may contain alkali metal atoms, such as sodium, potassium, cesium, etc., mainly derived from the raw materials. Of these, sodium, which can be easily removed, is not particularly limited, but potassium, cesium, etc., which are relatively difficult to remove, are preferably in a molar ratio to aluminum in the catalyst of 0.001 or more and 1.0 or less. In order to prevent damage to the zeolite framework, etc., caused by forcibly removing them from the catalyst, the molar ratio of potassium and / or cesium to aluminum in the catalyst is preferably in the above-mentioned range.
[0093] The specific surface area of the catalyst used in the present invention is as described above as the specific surface area of the zeolite. EXAMPLES
[0094] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the following examples in any way as long as the gist of the present invention is not exceeded. [Analysis and Evaluation] The analysis and performance evaluation of the zeolites obtained in the following Examples and Comparative Examples were carried out by the following methods.
[0095] [Powder XRD Measurement] <Sample preparation> Approximately 100 mg of zeolite sample was manually crushed using an agate mortar and placed in a sample holder of the same shape so that the sample amount was constant. <Instrument specifications and measurement conditions> The specifications of the powder XRD measurement device and the measurement conditions are as shown in Tables 1 and 2 below.
[0096] [Table 1]
[0097] [Table 2]
[0098] [Measurement of average primary particle size] The average primary particle size of the zeolite used in the present invention corresponds to the average particle size of the primary particles. The average primary particle size was determined by measuring the particle sizes of 30 randomly selected primary particles in particle observation using a scanning electron microscope, and averaging the particle sizes of the primary particles. The particle size was determined as the diameter of a circle having an area equal to the projected area of the particle (circle equivalent diameter).
[0099] [Analysis of Cu content and zeolite composition] The silicon atom content, aluminum atom content, and copper atom content in the zeolite standard sample were quantified by the following method. The zeolite sample was dissolved in a hydrochloric acid solution by heating, and the contents (mass%) of silicon, aluminum and copper atoms were determined by ICP analysis. Then, a calibration curve of the fluorescent X-ray intensity of the analyzed element in the standard sample and the atomic concentration of the analyzed element was created. Using this calibration curve, the contents (mass%) of silicon atoms, aluminum atoms, and copper atoms in the catalyst sample made of zeolite were determined by X-ray fluorescence analysis (XRF). ICP analysis was performed using an apparatus named ULTIMA 2C manufactured by Horiba, Ltd. XRF was performed using an apparatus named EDX-700 manufactured by Shimadzu Corporation.
[0100] [Evaluation of catalytic activity] The prepared catalyst sample was press-molded, crushed, sieved, and sized to 0.6 to 1 mm. 1 ml of the sized catalyst sample was packed into an atmospheric fixed-bed flow-type reactor. A gas having the composition shown in Table 3 below was fed into the catalyst bed at a space velocity of SV=60,000 h -1 The catalyst layer was heated while flowing nitrogen oxides through it. When the outlet NO concentration became constant at 300°C, the nitrogen oxide removal activity of the catalyst sample was evaluated based on the NO purification rate (%) calculated using the following formula: NO purification rate (%) = {(inlet NO concentration) - (outlet NO concentration)} / (inlet NO concentration) x 100
[0101] [Table 3]
[0102] [Example 1] [Zeolite synthesis] 4.0g of water, 5.4g of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (35% by mass aqueous solution, manufactured by Seichem Co., Ltd.) as an organic structure directing agent (SDA), and 0.8g of NaOH granules (manufactured by Wako Pure Chemical Industries, Ltd.) were mixed, and 0.29g of amorphous Al(OH)3 (Al2O3: 53.5% by mass, manufactured by Aldrich Co., Ltd.) was added and stirred to dissolve into a transparent solution. 8.9g of Snowtex 40 (silica concentration: 40% by mass, manufactured by Nissan Chemical Co., Ltd.) was added to this and stirred at room temperature for 5 minutes, after which 0.18g of uncalcined CHA-type zeolite (SiO2 / Al2O3 ratio = 22) was added as a seed crystal and stirred at room temperature for 2 hours to obtain a pre-reaction mixture.
[0103] This pre-reaction mixture was placed in a pressure-resistant container and hydrothermal synthesis was carried out for 3 days while rotating (15 rpm) in an oven at 170°C. After this hydrothermal synthesis reaction, the reaction liquid was cooled and the generated crystals were collected by filtration. The collected crystals were dried at 100°C for 12 hours, and then the XRD of the obtained zeolite powder was measured. It was confirmed that AEI-type aluminosilicate zeolite 1 was synthesized, which shows an XRD pattern with peaks and relative intensities at the positions shown in Table 4 in lattice spacing representation. The SiO2 / Al2O3 molar ratio of aluminosilicate zeolite 1 by XRF analysis was 15.
[0104] [Table 4]
[0105] [Catalyst preparation and evaluation of catalytic activity] In order to remove organic matter from the zeolite, the aluminosilicate zeolite 1 synthesized in Example 1 was calcined under an air stream at 600°C for 5 hours. Next, in order to remove Na ions from the calcined zeolite, the calcined zeolite was dispersed in a 1 mol / L aqueous solution of ammonium nitrate and subjected to ion exchange at 60°C for 5 hours. The zeolite was recovered by filtration and washed with ion-exchanged water three times. The ion exchange and washing were then repeated two more times. The obtained zeolite powder was dried at 100°C for 12 hours and NH4+ The aluminosilicate zeolite 2 was obtained. It was then calcined in air at 500°C for 2 hours and H + Aluminosilicate zeolite 3 of type was obtained.
[0106] Cu was supported by impregnation support treatment on aluminosilicate zeolite 3. 0.3 g of copper acetate (II) (Kishida Chemical Co., Ltd.) was dissolved in 20 g of water for 1 g of aluminosilicate zeolite 3 so that 10 mass % of Cu could be supported, to obtain an aqueous solution of copper acetate (II). Aluminosilicate zeolite 3 was dispersed in this aqueous solution of copper acetate (II), and water was removed by reduced pressure distillation using an evaporator while heating in a water bath at 50 ° C. After removing water, 10 g of ion-exchanged water was added and redispersed, and water was removed by reduced pressure distillation while heating in a water bath at 50 ° C. After removing water, 10 g of ion-exchanged water was added again and redispersed, and water was removed by reduced pressure distillation while heating in a water bath at 50 ° C. As described above, a total of three reduced pressure distillations were performed, and the impregnation support treatment was completed to obtain catalyst 1. XRF analysis of catalyst 1 revealed that the Cu / Al molar ratio was 0.8.
[0107] [Comparative Example 1] ZSM-5 (SiO2 / Al2O3 molar ratio: 40) manufactured by Tosoh Corporation was used to carry 4.0 mass% of Cu by vacuum distillation using an evaporator in the same manner as in Example 1, to obtain catalyst 2. XRF analysis of catalyst 2 revealed that the Cu / Al molar ratio was 0.75.
[0108] The evaluation results of the catalytic activity of catalyst 1 and catalyst 2 showed that the NO conversion rate of catalyst 1 was 39%, and that of catalyst 2 was 35%. The evaluation results of the catalytic activity of catalyst 1 and catalyst 2 are also shown in Figure 1. With regard to activity at low temperatures of about 300°C, which is considered important in exhaust gas treatment, it was found that catalyst 1 (shown as CAT-A in Figure 1) was a catalyst with higher activity than catalyst 2 (shown as CAT-B in Figure 1). In Figure 1, the NO conversion rate (%) is shown as "NO conversion (%)".
[0109] In general, 8-membered ring zeolites have smaller pore sizes than 10-membered ring zeolites, so that when metals are loaded, the pores are easily blocked by metals, making it difficult to increase the amount of metal that functions as an active site. For example, Table 1 in Non-Patent Document 1 shows the physical properties of Ferrierite (pore size: 5.4×4.2 Å) with pores smaller than ZSM-5 (pore size: 5.5×5.1 Å) after Cu ion exchange. Although the amount of Cu ion exchange in the zeolite is greater than that of ZSM-5, the amount of NO adsorption is less than that of ZSM-5, indicating that the amount of Cu available to serve as catalytic active sites is less than that of ZSM-5. Therefore, in zeolites with pore sizes smaller than ZSM-5, excessive loading of Cu to the extent that the ion exchange rate exceeds 100% is not usually considered. On the other hand, the 8-membered ring zeolites used in the present invention all have smaller pore sizes than ZSM-5, but they exhibit high catalytic activity when Cu, which acts as an active site, is supported at Cu / Al=0.5 (ion exchange rate 100%) or more. This is described on page 579 of Non-Patent Document 1 as follows: + -Cu + The dimer is considered to be the active site in this reaction system, but in the case of the 8-membered ring zeolite of the present invention, the pore size is small, so the distance between the adjacent Al is short, and the distance between the Cu supported on the Al is also short, so the Cu is more effective in catalytic activity. + -Cu + It is believed that this facilitates the formation of dimers, which has the effect of achieving higher activity rather than being influenced by pore blockage. [Industrial Applicability]
[0110] The present invention provides a method for converting nitrogen oxides contained in factory and automobile exhaust gases into harmless substances by using a catalyst with excellent processing capacity. In particular, since it can be used in places where it is difficult to establish an infrastructure for reducing agents, it can be applied in a wide range of environments.
Claims
1. A method for purifying nitrogen oxides in a gas by contacting the nitrogen oxides with a zeolite carrying copper as a metal, the method comprising the steps of: The zeolite is an aluminosilicate zeolite having an 8-membered ring structure with a maximum pore size, the zeolite has a SiO 2 / Al 2 O 3 (molar ratio) of 3 to 100, and the molar ratio of the amount of metal supported to Al in the zeolite is 0.65 to 2.0; using a reducing agent having a molar ratio of 0.1 or less to the nitrogen oxides contained in the gas, A method for purifying nitrogen oxides, characterized in that the space velocity of exhaust gas in said method for purifying nitrogen oxides is 10,000 hr -1 or more.
2. 2. The method for purifying nitrogen oxides according to claim 1, wherein the zeolite is any one of AEI type, CHA type, AFX type, and RHO type.
3. 3. The method for purifying nitrogen oxides according to claim 1, wherein the amount of the metal supported on the zeolite is 1.0 to 20% by mass based on the total amount of the catalyst.
4. 4. The method for purifying nitrogen oxides according to claim 1, wherein the amount of nitrogen oxides in the gas is 10 to 10,000 ppm by volume.
Citation Information
Patent Citations
Nitrogen oxide contact decomposing catalyst, its preparation and use
JP1990164451A
Method and system for purifying exhaust gases from internal combustion engines
JP2015516882A
AEI zeolite and manufacturing method and application thereof
JP2017081809A
AEI structure molecular sieve and its manufacturing method and use
JP2020529964A